2001
DOI: 10.1073/pnas.98.2.641
|View full text |Cite
|
Sign up to set email alerts
|

Point mutations in the murine fumarylacetoacetate hydrolase gene: Animal models for the human genetic disorder hereditary tyrosinemia type 1

Abstract: Hereditary tyrosinemia type 1 (HT1) is a severe autosomal recessive metabolic disease associated with point mutations in the human fumarylacetoacetate hydrolase (FAH) gene that disrupt tyrosine catabolism. An acute form of HT1 results in death during the first months of life because of hepatic failure, whereas a chronic form leads to gradual development of liver disease often accompanied by renal dysfunction, childhood rickets, neurological crisis, and hepatocellular carcinoma. Mice homozygous for certain chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
1
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 38 publications
2
53
1
1
Order By: Relevance
“…Mutations in FAH disrupt tyrosine catabolism (Fig. 1) and lead to the accumulation of fumarylacetoacetate (FAA), maleylacetoaetate (MAA), succinylacetoacetate (SAA), MA and FA in liver and kidney that are believed to be responsible for the hepato-renal manifestations of the disease [6]. The accumulated SAA is readily converted to SA which inhibits a proximal step in heme synthesis and leads to the build up of the putative nerotoxin ␊-aminolevulinate (␊-ALA).…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in FAH disrupt tyrosine catabolism (Fig. 1) and lead to the accumulation of fumarylacetoacetate (FAA), maleylacetoaetate (MAA), succinylacetoacetate (SAA), MA and FA in liver and kidney that are believed to be responsible for the hepato-renal manifestations of the disease [6]. The accumulated SAA is readily converted to SA which inhibits a proximal step in heme synthesis and leads to the build up of the putative nerotoxin ␊-aminolevulinate (␊-ALA).…”
Section: Introductionmentioning
confidence: 99%
“…Such a case was reported in a mouse model for the remedy for human hereditary tyrosinemia type I (HTI), which is a fatal recessive genetic disease caused by mutation of an essential gene in the tyrosine catabolic pathway, fumarylacetoacetate hydrolase (FAH) [25]. The mouse model for human HTI, called Fah5981SB mouse strain, carries a G>A point mutation at the boundary of exon 8 and intron 8 of Fah locus [26], which leads to aberrant splicing of mRNA. Fah deficiency causes accumulation of toxic metabolites in hepatocytes and leads to liver damage and body weight loss.…”
Section: Remedy Of Diseases In Mice Harboring Mutations By Nucleotidementioning
confidence: 99%
“…Studies on human HT1 and its animal models have shown that the accumulation of MAA, FAA, succinylacetoacetate, and succinylacetone causes direct tissue damage (Lindblad et al, 1977;Grompe et al, 1993;Sun et al, 2000;Aponte et al, 2001;Jorquera and Tanguay, 2001;Bergeron et al, 2006). In this study, we found that treatment of Arabidopsis wild-type seedlings with succinylacetone is able to mimic the sscd1 cell death phenotype (Fig.…”
Section: Discussionmentioning
confidence: 48%
“…In both human HT1 and mouse fah mutants, the metabolic intermediates (MAA, FAA, succinylacetoacetate, and succinylacetone) were highly accumulated, which are toxic to cells and tissues (Lindblad et al, 1977;Grompe et al, 1993;Aponte et al, 2001;Jorquera and Tanguay, 2001). Due to technical difficulties, it is so far not possible to detect these metabolic intermediates in entire worms (Fisher et al, 2008) and in Arabidopsis plants (data not shown).…”
Section: Succinylacetone Induces Cell Death In Arabidopsismentioning
confidence: 99%